Pengembangan Potensi Pertanian dalam Program Penanganan Akses Reforma Agraria (Para) di Kabupaten Blora - Arnanto, Ardhi; Suprianti, Theresia; Farid, Abdul Haris (Jurnal Pertanahan, 2025)
Dryland farming dominates Blora Regency, with a high level of critical land, resulting in low productivity and low farmer incomes. Most farmers have small plots of land and face limited subsidized fertilizer, minimal irrigation, and fluctuating crop prices. This study aims to examine the Agrarian Reform Access Handling Program (PARA) in improving farmer welfare in the region. The method used was qualitative research, located in Sumurboto, Wantilgung, and Tempuran Villages. Primary data were collected through interviews with 300 PTSL participants from 2016–2020. The results indicate that the majority of farmers have low education and earn less than IDR 1,500,000 per month, far below the Blora Regency minimum wage in 2024. Although the PTSL program has provided legal land ownership, most recipients have not utilized their certificates to gain access to capital from financial institutions. Training programs such as manure production, agricultural product processing, and strengthening farmer groups have shown positive results but have not significantly increased income. To achieve sustainable farmer independence and welfare in Blora Regency, we need to further evaluate the strategy and implementation of the PARA Program. Pertanian lahan kering mendominasi wilayah Kabupaten Blora dengan tingkat lahan kritis yang tinggi, menyebabkan produktivitas rendah dan pendapatan petani kecil. Sebagian besar petani memiliki lahan sempit, menghadapi keterbatasan pupuk subsidi, minimnya irigasi, serta fluktuasi harga hasil panen. Penelitian ini bertujuan menelaah Program Penanganan Akses Reforma Agraria (PARA) dalam meningkatkan kesejahteraan petani di wilayah tersebut. Metode yang digunakan adalah penelitian kualitatif dengan lokasi di Desa Sumurboto, Wantilgung, dan Tempuran. Data primer dikumpulkan melalui wawancara terhadap 300 peserta PTSL tahun 2016–2020. Hasil menunjukkan mayoritas petani berpendidikan rendah dan berpenghasilan kurang dari Rp1.500.000 per bulan, jauh di bawah UMR Kabupaten Blora tahun 2024. Meskipun program PTSL telah memberikan legalitas kepemilikan tanah, sebagian besar penerima belum memanfaatkan sertipikatnya untuk memperoleh akses permodalan dari lembaga keuangan. Program pelatihan seperti pembuatan pupuk kandang, pengolahan hasil pertanian, dan penguatan kelompok tani menunjukkan hasil positif namun belum signifikan meningkatkan pendapatan. Kesimpulannya, diperlukan evaluasi lanjutan terhadap strategi dan pelaksanaan Program PARA untuk mewujudkan kemandirian dan kesejahteraan petani secara berkelanjutan di Kabupaten Blora.